Economics of hail protection net installation in super intensive apple orchards - Szabó, Viktor (Acta Agraria Debreceniensis, 2016)
The main objective of this study was to determine and organize beneficial and detrimental effects of hail protection nets, and as far as possible to quantify their economic impact. The main factors were determined, through which hail protection nets can affect the costs and incomes of the production, and as their sum the economic result. Considering these factors together with the investment cost and the annual maintenance costs allows the economic evaluation of purchasing of hail protection nets. The analysis was carried out using a deterministic simulation model based on primary data collection from apple producing businesses. Installing hail protection nets as additional technological elements of intensive apple orchards can be concluded by all means as an economic investment – trough their protective effect. However, to achieve really favourable economic indicators, definitely bigger tree height is needed making possible the realisation of around 8.0 t ha-1 extra yield. The main root of this phenomena are obviously the extremely high investment costs of hail protection nets, which result in a large mass of fixed costs during the production period. Therefore the basic economic interest is reaching higher yields and thereby higher profits per unit area.